(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study sought to determine the awareness level of SMEs managers’ on the influence of socio-cultural environmental forces on their business operations in Anambra State. One research question and two null hypotheses guided the study. Descriptive survey design was adopted. The research population comprise of 811 managers of small and medium enterprises registered with the Anambra State Ministry of Commerce and Industry. A sample size of 243 SMEs managers was selected for the study using proportionate stratified random sampling. A structured and validated five point rating scale questionnaire containing 10 items was used for data collection. Cronbach Alpha method was used to establish the reliability of the instrument which yielded coefficient of 0.85. The researchers administered the instrument with the help of three research assistants in the state. Data collected were analyzed using mean and standard deviation to answer the research question while ttest and Analysis of Variance (ANOVA) were employed to test the hypotheses at 0.05 level of significance. Findings revealed that SMEs managers’ in Anambra State were highly aware of the influence of socio-cultural environmental forces on their business operations. The study further revealed that gender and years of experience were not significant factors on the SME managers awareness level of the influence of sociocultural forces on their business operation. It was concluded that majority of the owners of SMEs in Anambra State understands the importance socio-cultural environmental forces can play in success of their business operations and are conscious of the changes in the business that could result as a result in these sociocultural forces. The researchers recommended among others that SME managers should constantly review, modify and develop new policies in line with changes in socio-cultural environmental forces. This is because high awareness alone without proper implementation of policies cannot guarantee business success. SMEs managers should engage in regular market research in order to recognize current needs, value, taste and preference of the type of goods consumers are looking for in the marketplace.